Understanding the Attitude-Behavior Gap for Renewable Energy Systems Using Behavioral Reasoning Theory - Claudy, Marius C.; Peterson, Mark; O’Driscoll, Aidan (Journal of macromarketing, 2013)
Consumer adoption of renewable energies is an important step towards less carbon-intensive and more sustainable energy systems. But despite growing ecological awareness and articulated preferences for green products, renewable energies face slow rates of diffusion in consumer markets. This has been hard to explain given consumers’ favorability to the concept of products that lower one’s impact on the natural environment. This study uses data from 254 homeowners in Ireland to investigate the psychological process of adopting a renewable energy system – solar energy panels. Applying Behavioral Reasoning Theory (BRT), this research examines a proposed model in which reasons both for and against adopting solar panels mediate the relationship between consumers’ attitudes, values and adoption intentions. Results suggest the model is generally supported with both reasons for adoption and reasons against adoption having countervailing influences in the psychological processing of adoption intentions. These findings suggest that researchers and marketers should include mediating constructs, such as (i) reasons for adoption, (ii) reasons against adoption, and (iii) attitudes toward a technology when attempting to explain how consumers think about the adoption of renewable energy systems.